PENERAPAN MODEL PEMBELAJARAN LANGSUNG (DIRECT INTRUKTION) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III.C SDN 2 GAJAH SAKTI KECAMATAN MANDAU KABUPATEN BENGKALIS - Meri Yusmanti; Hamizi Hamizi; Erlisnawati Erlisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem in this research is the student achievement of Sains studies third graderes (III.C) SDN 2 Gajah Sakti Kecamatan Mandau Kabupaten Bengkalis still low with an average value of 66,66 and minimum completenness criteria (KKM) Natural studies is 70.The purpose of this research was to improve the students achievement of the third graders (III.C) SDN 2 Gajah Sakti Kecamatan Mandau Kabupaten Bengkalis with the implementation Direct Intruction model. This research is Classroom action Research (CAR) with two cycles in second semester 2014/2015. Before implementation of Direct Intruction model, average from the base score 66,66 After implementation of Direct Intruction model, UH I was 79 that improve 12,34 % from before exam with average 66,66 UH II was 82,67 that improve 16,01 %. Teacher’s activities with the implementation of type Direct Intruction model at first meeting of first cycle was 65 % (enough category), and second meeting was 70 % (good category). At second cycle, teacher’s activities at first meeting was 80 % (good category) and second meeting was 90 % (best category). Students activities at first meeting of first cycle was 65% (enough category) and second meeting was 80 % (good category). At second cycles, students activities at first meeting was 85%(good category) and second meeting was 90 % (best category). Implementation type Direct Intruction model can improved Sains studies students achievement of thied graderes (III.C) SDN 2 Gajah Sakti Kecamatan Mandau Kabupaten Bengkalis.Key Words : Direct Intruction Model, Sains Studies Student’s Achievement.